แอคติโนแบคทีเรียจากไบรโอไฟต์ และความสามารถในการสร้างสารส่งเสริมการเติบโตของพืช - ชฎาพร อินสุข (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This study was designed to investigate the cultivable actinobacteria associated with bryophytes and their plant growth promoting ability. 126 actinobacteria were tested for their ability to promote growth of plant in vitro and in plants. These isolates could produce IAA and siderophores and could solubilize phosphate. All isolates were identified by 16S rRNA gene sequences analysis. They were members of the genus Micromonospora, Streptomyces, Mycolicibacterium, Cryptosporangium, Nocardia, Saccharothrix, Actinoplanes, and Streptosporangium. Strain CMU55-4, which shared 98.47% of ANIb values and 91.8% digital DNA-DNA hybridization to Micromonospora chalcea DSM 43026T, was characterized for the plant growth promoting activities through genome mining. The draft genome size was 6.6 Mb (73% GC). The genome contained 5,933 coding sequences. Functional annotation of the genes predicted that encoded genes essential for siderophore production, phosphate solubilization that enable bacteria to survive under nutrient limited environment. Also, glycine-betaine accumulation and trehalose biosynthesis to aid plant under drought stress. Micromonospora sp. CMU55-4 also exhibited genes for various carbohydrate metabolic pathways indicating that it can efficiently utilize carbohydrates inside plant cells. Additionally, heat shock proteins, cold shock proteins, and oxidative stress conferring genes such as glutathione biosynthesis were identified. When this bacterial strain was introduced to moss, strain CMU55-4 could increase the amount of carotenoid, fresh weight, and dry weight of Physcomitrium sphaericum (C. Ludw.) Fürnr., promote capsule production, and could rescue P. sphaericum gametophytes during acclimatization to soil.